A Porous Zirconium‐Based Metal‐Organic Framework with the Potential for the Separation of Butene Isomers. Issue 42 (6th September 2016) - Liu, Huimin; He, Yabing; Jiao, Jingjing; Bai, Dongjie; Chen, De‐li; Krishna, Rajamani; Chen, Banglin
Abstract: By using a novel C 3 ‐symmetrical tricarboxylate (4, 4′, 4′′‐benzene‐1, 3, 5‐triyl‐1, 1′, 1′′‐trinaphthoic acid), a novel zirconium‐based metal‐organic frameworkZJNU‐30 was solvothermally synthesized and structurally characterized. Single‐crystal X‐ray structural analyses show thatZJNU‐30 consists of Zr6 ‐based nodes connected by the organic linkers to form a (3, 8)‐connected network featuring the coexistence of two different polyhedral cages: octahedral and cuboctahedral cages with the dimensions of about 14 and 22 Å, respectively. Remarkably, ZJNU‐30 is very stable when exposed to air for one month. More importantly, with a moderately high surface area, hierarchical pore structures, and an aromatic‐rich pore surface in the framework, ZJNU‐30, after activation, exhibits a promising potential for the selective adsorptive separation of industrially important butene isomers consisting of cis ‐2‐butene, trans ‐2‐butene, 1‐butene, and iso ‐butene at ambient temperature. This separation was established exclusively by gas adsorption isotherms and simulated breakthrough experiments. To the best of our knowledge, this is the first study investigating porous metal‐organic frameworks for butene‐isomer separation. Abstract : MOFs in the butene business : We report the first zirconium‐based metal‐organic framework constructed from a triangular tricarboxylate ligand exhibiting a promising potential for the separation of butene isomers, which is very difficult in petrochemical processing.